(untitled) (Sebha University Conference Proceedings, 2024)
Study the possibility of using a smart farm based on solar system as the first source of electricity in Libya, as an economical solution, and we will study the monthly climate in Libya for the average temperature. And the amount of electrical power required and the efficiency of use; to design a solar system with an appropriate capacity to cover all the needs of the farm. And we will rely on (Internet of Things) technology in this farm to control it remotely. A soil moisture sensor will be used to monitor the moisture content of the soil; a float water level sensor will be used to monitor the water level in the tank; and a 16 x 12 LCD will be used to display the soil and tank status and turn on the water pump when the moisture content of the soil falls below a predetermined level, provided there is enough water in the tank.